2016
DOI: 10.1016/j.cmet.2016.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of Cytosolic One-Carbon Flux Compensates for Loss of the Mitochondrial Folate Pathway

Abstract: SummaryOne-carbon (1C) units for purine and thymidine synthesis can be generated from serine by cytosolic or mitochondrial folate metabolism. The mitochondrial 1C pathway is consistently overexpressed in cancer. Here we show that most but not all proliferating mammalian cell lines use the mitochondrial pathway as the default for making 1C units. CRISPR-mediated mitochondrial pathway knockout activates cytosolic 1C-unit production. This reversal in cytosolic flux is triggered by depletion of a single metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
235
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(254 citation statements)
references
References 31 publications
18
235
1
Order By: Relevance
“…Similarly, in the Ras-driven lung cancer cell line A549, we obtain αoxPPP = 82±4%. In contrast, in the Ras-driven pancreatic cancer cell line 8988T, where both malic enzyme 1 14 and the folate enzyme MTHFD1 have been implicated as significant cytosolic NADPH producers 15 , and in differentiated 3T3-L1 adipocytes where malic enzyme is a major NADPH producer 16 , αoxPPP < 50%. In immortalized pluripotent stem cells, prior literature has reported > 50% NADPH labeling from 3- 2 H-glucose, suggesting slower exchange between water and NADPH in that cell type 17 .…”
mentioning
confidence: 97%
“…Similarly, in the Ras-driven lung cancer cell line A549, we obtain αoxPPP = 82±4%. In contrast, in the Ras-driven pancreatic cancer cell line 8988T, where both malic enzyme 1 14 and the folate enzyme MTHFD1 have been implicated as significant cytosolic NADPH producers 15 , and in differentiated 3T3-L1 adipocytes where malic enzyme is a major NADPH producer 16 , αoxPPP < 50%. In immortalized pluripotent stem cells, prior literature has reported > 50% NADPH labeling from 3- 2 H-glucose, suggesting slower exchange between water and NADPH in that cell type 17 .…”
mentioning
confidence: 97%
“…Methylene-THF reductase converts cytosolic CH 2 -THF into CH 3 -THF. However, in most proliferating cultured cells, the mitochondrial pathway is used (Ducker et al 2016). The one-carbon unit in mitochondrial CH 2 -THF can leave the mitochondrion as formate and enter the cytosolic folate cycle via N 10 -formyl-THF (10-fTHF) synthesis (Figs.…”
Section: Synthesis Of the Universal Methyl Donor Sammentioning
confidence: 99%
“…Knockdown of MTHFD2 in breast cancer cells suppressed proliferation and induced apoptosis (20). Multiple studies indicated that the folate cycle is an important metabolic pathway crucial to cancer growth (11,20,(22)(23)(24). A recent study showed that the folate cycle, through NADPH production, enabled melanoma cells to endure oxidative stress during metastasis (25).…”
Section: Introductionmentioning
confidence: 99%